Global Regulation of Cybercrime through International Law and Cyberconventions - Enver Buçaj; Arsim Thaqi (Kriminologie - Das Online-Journal)
Background: This study examines the necessity of regulating cybercrime through international law and treaties, emphasising the role of the Budapest Convention as a foundational agreement. It explores the perception of global realities of cyberspace, prospects for legislative harmonization, and an international response to the legal status of the problem. The study highlights the urgent need to regulate cybercrime within the framework of international criminal law because of its persuasive threats across the globe. In terms of method, it uses normative legal research, analysing the international legal foundations based on the Budapest Convention and contrasting them with other types of comparative legal reasoning in and outside of the European Union. Technological insight is also looked at with a view to monitoring existing programs and recommending more effective mechanisms to combat cybercrime. Foremost among the findings is the irrefutable need for a legally interned unified world system of legal framework to fight cybercrime. The Budapest Convention serves as a starting point, while the ever-morphing nature of threats justifies the development of newer legal norms through the continuous transformation of reactive law. It discusses the need for uniform definitions of the law, better interaction between the public and private sectors, and better ethical definitions and practices of data collection and dissemination.